Exploitations of Schiff's test and iodoform test for an effective quality assessment of alcohol-based hand sanitizers - Prakobdi C. (2023)
In the period of the corona virus disease 2019 (COVID-19) outbreak, an alcohol-based hand sanitizer is one of the most in-demand products for disinfection purposes. Two major concerns are adulteration of methanol, which causes toxicity to human health, and the concentration of legal alcohol in hand sanitizers due to their effect on antivirus. In this work, the first report of the entire quality assessment of alcohol-based hand sanitizers in terms of detection of methanol adulteration and quantification of ethanol is presented. Detection of adulterated methanol is carried out based on Schiff's reagent after the oxidation of methanol to formaldehyde, giving a bluish-purple solution to detect at 591 nm. In cases where a colorless solution is observed, an iodoform reaction with turbidimetric detection is then performed for quantitative analysis of legal alcohol (ethanol or isopropanol). To comply with the regulation of quality assessment of alcohol-based hand sanitizers, a regulation chart with four safety zones is also presented, employing a combination of two developed tests. The coordinates of a point (x, y) obtained from the two tests are extrapolated to the safety zone in the regulation chart. The regulation chart also showed consistency of analytical results as compared with the gas chromatography-flame ionization detector.